2023
DOI: 10.1186/s40854-023-00506-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sustainability on financial distress in the air transport industry: the moderating effect of Asia–Pacific

Abstract: The tremendous impact of the coronavirus pandemic on the global aviation industry has led to many cases of airline financial distress and bankruptcy. The Asia–Pacific region (APAC) contains more than half of the world’s population, and its airlines had the highest profit margin of any region. In this study, we investigate whether corporate sustainability practice can reduce the financial distress risk of air carriers, and, if so, what would the effect be in APAC? We first examine the relationship between envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…The inclusion of "ESG" suggests that airlines are increasingly being evaluated not just on their environmental initiatives but on a broader range of social and governance issues [69][70][71]. This includes discussions around diversity and inclusion, ethical governance practices, and how these areas are integrated into corporate strategy and reporting.…”
Section: Emerging Trendsmentioning
confidence: 99%
“…The inclusion of "ESG" suggests that airlines are increasingly being evaluated not just on their environmental initiatives but on a broader range of social and governance issues [69][70][71]. This includes discussions around diversity and inclusion, ethical governance practices, and how these areas are integrated into corporate strategy and reporting.…”
Section: Emerging Trendsmentioning
confidence: 99%
“…They concluded that ESG disclosure reduces default risk for enterprises by enhancing profitability, reducing performance variability, and lowering the cost of debt. Moreover, based on the recent years hit by COVID-19, Jin et al (2023) and Reber et al (2022) found that firms with higher ESG disclosure received higher returns and experienced lower downside risk.Similarly, the relationship between ESG disclosure and financial distress risk has received scholarly attention, particularly as many airlines worldwide faced financial distress and bankruptcy due to COVID-19(Shi et al, 2023). The authors contend that environmental actions could increase financial distress risk, while improving social and governance activities can reduce it.…”
mentioning
confidence: 99%
“…In the literature, the majority of studies focused on US airline financial distress and Altman Z-score (1968) are mostly applied (Alan & Lapré, 2018;Davalos et al, 1999;Gritta, 1982;Lu et al, 2014;Ribbink et al, 2011;Stepanyan, 2014). While previous studies have utilized the Altman Z-score model for European airlines (Shi et al, 2023;Shi & Li, 2021), a comprehensive analysis of its predictive power has been lacking. To address the existing gap in the literature regarding the accuracy of updated Z-score models on European airline companies, in this present study, we assess the predictive capacity of the updated Altman models as applied to European air carriers.…”
mentioning
confidence: 99%